Structure of hen lysozyme in solution. - Smith, L; Sutcliffe, M; Redfield, C; Dobson, C (1993)
The structure of the 129-residue protein hen lysozyme has been determined in solution by two-dimensional 1H nuclear magnetic resonance methods. 1158 NOE distance restraints, and 68 phi and 24 chi 1 dihedral angle restraints were employed in conjunction with distance geometry and simulated annealing procedures. The overall C alpha root-mean-square deviation from the average for 16 calculated structures is 1.8(+/- 0.2) A, but excluding 14 residues in exposed disordered regions, this value reduces to 1.3(+/- 0.2) A. Regions of secondary structure, and the four alpha-helices in particular, are well defined (C alpha root-mean-square deviation 0.8(+/- 0.3) A for helices). The main-chain fold is closely similar to structures of the protein in the crystalline state. Furthermore, many of the internal side-chains are found in well-defined conformational states in the solution structures, and these correspond well with the conformational states found in the crystal. The general high level of definition of mainchain and many internal side-chains in the solution structures is reinforced by the results of an analysis of coupling constants and ring current shifts. Many side-chains on the surface, however, are highly disordered amongst the set of solution structures. In certain cases this disorder has been shown to be dynamic in origin by the examination of 3J alpha beta coupling constants.